2005
DOI: 10.1007/s10482-004-3194-y
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus vadensis, a new species of the group of black Aspergilli

Abstract: A strain from the group of black Aspergilli was analysed in detail to determine the species to which it belongs. A detailed analysis of morphology, RFLP patterns and metabolite profiles was carried out. In addition, a phylogenetic tree was constructed for the black Aspergilli using the ITS and the b-tubulin sequences of the individual strains. The new species differs by its poor growth on glycerol and galacturonate and its unique extrolite profile consisting of aurasperone B, nigragillin, asperazine and kotani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 20 publications
3
30
0
1
Order By: Relevance
“…for distinct Aspergillus sections, as recommended by Pitt and Taylor (2014). If the latter solution to the nomenclatural problem in Aspergillus sensu Raper and Fennell (1965) was to be adopted, Aspergillus will have to be neo-typified, by for example A. niger (Pitt and Taylor 2014), because Aspergillus at Table 1 Sections of Aspergillus and their associated sexual states Subgenus/section Raper and Fennell (1965) group Earlier name given to the sexual state in the two-name system References on taxonomy, phylogeny and secondary metabolites Circumdati/Nigri Aspergillus niger group Saitoa, now informally saitoa-morph Parenicová et al 2001;Abarca et al 2004;Samson et al 2004;De Vries et al 2005;Serra et al 2006;Perrone et al 2007Perrone et al , 2008Samson et al 2007a, b;Varga et al 2007a;Noonim et al 2008;Nielsen et al 2009;Varga et al 2011a;Meijer et al 2011;Perrone et al 2011;Jurjevic et al 2012a, b;Hong et al 2013;Horn et al 2013 Circumdati/Flavi…”
Section: Taxonomy and Phylogeny Of Aspergillusmentioning
confidence: 99%
“…for distinct Aspergillus sections, as recommended by Pitt and Taylor (2014). If the latter solution to the nomenclatural problem in Aspergillus sensu Raper and Fennell (1965) was to be adopted, Aspergillus will have to be neo-typified, by for example A. niger (Pitt and Taylor 2014), because Aspergillus at Table 1 Sections of Aspergillus and their associated sexual states Subgenus/section Raper and Fennell (1965) group Earlier name given to the sexual state in the two-name system References on taxonomy, phylogeny and secondary metabolites Circumdati/Nigri Aspergillus niger group Saitoa, now informally saitoa-morph Parenicová et al 2001;Abarca et al 2004;Samson et al 2004;De Vries et al 2005;Serra et al 2006;Perrone et al 2007Perrone et al , 2008Samson et al 2007a, b;Varga et al 2007a;Noonim et al 2008;Nielsen et al 2009;Varga et al 2011a;Meijer et al 2011;Perrone et al 2011;Jurjevic et al 2012a, b;Hong et al 2013;Horn et al 2013 Circumdati/Flavi…”
Section: Taxonomy and Phylogeny Of Aspergillusmentioning
confidence: 99%
“…This indicates that bis-naphtho-γ-pyrones should have taxonomic significance which needs to be further investigated [41]. Each fungal species also needs to be clearly identified [48][49][50].…”
Section: Bis-naphtho-γ-pyronementioning
confidence: 99%
“…Phylogenetic analyses of sequences of the internal transcribed spacers region (ITS), the 5.8S rRNA gene and the D1-D2 region of the 28S rRNA gene indicated that, in addition to A. niger and A. tubingensis, at least five other species belong to section Nigri: Aspergillus heteromorphus, Aspergillus ellipticus, Aspergillus carbonarius, Aspergillus japonicus and Aspergillus aculeatus (Varga et al, 2000;Parenicova et al, 2001). Several other black Aspergillus species have been described recently, including Aspergillus vadensis (de Vries et al, 2005), Aspergillus costaricaensis, Aspergillus piperis, Aspergillus lacticoffeatus and Aspergillus sclerotioniger (Samson et al, 2004), Aspergillus ibericus (Serra et al, 2006) and Aspergillus brasiliensis (Varga et al, 2007).…”
Section: Introductionmentioning
confidence: 99%